Investigation of Nurses' Opinions on Foreign Nationality Patient Care - Seher Yurt; Sevim Şen (Association of Nurse Managers, 2021)
INTRODUCTION: This research has been planned to examine the professional and institutional preparations of nurses for foreign patients, and to identify the difficulties they experience regarding their care. METHODS: The descriptive study was carried out in two private hospitals in Istanbul. 180 volunteer nurses participated in the study. The data were collected using the Information Form created by the researchers. Frequency, percentage and chi square test were used in the analysis of the data. RESULTS: It has been determined that 62.8% of the nurses' foreign language is insufficient, 67.2% of foreign students negatively affect nursing care practices, undergraduate graduates nurses, those who know a foreign language and those who work less than five years have less difficulty in the care of foreign students. DISCUSSION AND CONCLUSION: It was demonstrated that they were unable to communicate with the patient and their relatives, therefore the data collection process from the patient was negatively affected and affected other processes. For this reason, it is recommended that schools provide a supportive environment to students, in practice, and administrators and nurses to provide guidance, create continuing education resources, provide care procedures and communication resources during the learning process.